The Numismatic Evidence of the Mongol Invasion in the wider Split Region in march, 1242 (Archaeologia Adriatica, 2022)
In this paper the authors reinterpret a number of long known hoards from central Dalmatia containing mostly communal coins of Split, associating their hiding with March 1242, when Bela IV, king of Hungary and Croatia escaped to the Adriatic chased bythe Mongols. The Mongol invasion could also explain certain individual coin finds from caves in southeastern Lika and northern Dalmatia that could have been used as temporary shelters for the local population.